PENGARUH MANFAAT PROTEKSI DAN INVESTASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN ASURANSI PENDIDIKAN SMART KIDZ AXA FINANCIAL INDONESIA CABANG PEKANBARU - Laila, Yoma; ', Sumarno; ', Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: this research aims to investigate the influence of protection benefits and investment benefits against purchasing decisions on insurance education Smart Kidz AXA Pekanbaru. This research was conducted at PT. AXA Financial Indonesia branch Pekanbaru. Sample is determined by saturated technique with a sample of 34 custumers. Data is collected by questionnaire method. The method of data analysis used multiple linear regression . The results obtained F-value (10.356)> F-table (3.33) means simultaneously protection benefits and investment benefits have a positive and significant impact on the purchasing decision on insurance education Smart Kidz AXA Pekanbaru. While partially, protection benefits significantly influence purchasing decisions education and investment benefits do not affect significantly to purchasing decisions on insurance education Smart Kidz. This is proven by the regression coefficient, regression coefficients of variable protection benefits is 0.428 and investment benefits is 0.048. The value of the coefficient of determination is obtained 0.313 means both variables may explain purchasing decisions on insurance education Smart Kidz of 31.3% and the rest of 68.7% explained by other factors not examined.Key words: protection benefits, investment benefits, purchasing decision, insurance